(untitled) (Research, Society and Development, 2024)
The upper labial frenum or frenulum consists mainly of a triangular fibrous or fibromuscular tissue, located in the midline between the upper central incisors. The frenulum can cause consequences for the patient, mainly highlighting the presence of the median diastema, generating dental disharmony and altering the smile, consequently affecting self-esteem and interfering with the patient’s social life. Frenectomy, which consists of repositioning the hypertrophic labial frenulum, is the procedure indicated to correct this tissue structure. However, the objective of this study is to present a follow-up of the surgical approach of upper lip frenectomy in a child in the mixed dentition phase. Through clinical examination, the presence of a wide, voluminous upper labial frenulum, papilla ischemia at the time of lip traction and the presence of diastema between the incisors was observed. After the clinical examination, it was found that there was a need for surgical intervention to correct the upper labial frenulum. The proposed treatment is surgical repositioning of the brake. Therefore, the proposed treatment favored the preservation of the functional, anatomical and aesthetic characteristics of the upper labial frenulum.